THU0636 Canakinumab treatment in adult-onset still's disease: case series. (12th June 2018) - Ugurlu, S.; Guzelant, G.; Yurttas, B.; Ergezen, B.; Dalkilic, E.; Kasifoglu, T.; Yagiz, B.; Ozdogan, H.
Abstract : Background: In Adult-onset Still's disease (AOSD), cases refractory to typical DMARDs, Canakinumab (an anti-IL-1ß monoclonal antibody) has been reported to be effective in a limited number of refractory cases. 1 Objectives: The aim of this retrospective study was to represent AOSD patients treated with Canakinumab in 3 centres. Methods: The follow up data of 10 AOSD patients (8 female, 2 male), who were followed up in outpatient clinics of 3 tertiary centres were reviewed retrospectively. The initial characteristics and follow up findings were reported. Results: The mean timespan between the initial diagnosis and Canakinumab treatment 45.2±29 months (mean ±SD). Before the onset of Canakinumab therapy, all patients were exposed to methotrexate, 1 to leflunomide, 8 to Tocilizumab and 8 to Anakinra. As for the biologic agents, 3 patients were also treated beforehand with Infliximab, 2 with Adalimumab, 2 with Etanercept and 2 with Rituximab. Canakinumab therapy was initiated in all patients with the indication of refractory disease under other medications, except for the one in whom neutropenia became evident under anakinra. The mean number of Canakinumab injections was 9.3±8. The mean follow-up period of patients treated with Canakinumab was 43.1±33 months. Seven out of 10 patients are still being treated with Canakinumab of 150 mg/month and one of 150 mg/every 2 months. One patient had a single injection and was fully controlled. The mean ferritin measure of 9 patients was reduced from 1292.3±1530 ng/ml to 354±530.2 ng/ml following the Canakinumab therapy (p=0.035). The mean of patient-reported global visual analogue scale (PG-VAS) scores was reduced from 7.4±2.4 to 2.3±2.2 with Canakinumab (p<0.001). Mean Erythrocyte sedimentation rate (ESR) was reduced from 44.2±35.1 to 22.7±26.5 with the help of Canakinumab therapy (p=0.005). Six patients are still on prednisolone at a maximum dose of 10 mg/day. The indication of therapy termination in the remaining 1 patient was the diagnosis of tuberculosis at 9th month of the treatment despite isoniazid prophylaxis. The patient was also treated with multiple biological agents beforehand, therefore it is not easy to conclude that treatment with Canakinumab induces tuberculosis flares. Conclusions: Canakinumab treatment seems to be effective in refractory AOSD patients who were previously treated with various agents. We state that an IL-1 blocking agent, Canakinumab is a relatively safe and effective alternative in managing refractory AOSD cases. On the other hand, randomised controlled trials are needed to further investigate the role of Canakinumab in these cases as well as its use as the first choice of biologic agents. Reference: [1] Kontzias A, Efthimiou P. The use of Canakinumab, a novel IL-1β long-acting inhibitor, in refractory adult-onset Still's disease. Semin Arthritis Rheum2012;42(2):201–5. Disclosure of Interest: None declared